Effect of Dose And Time of Npk Fertilizer Application on The Growth And Yield of Tomato Plants (Lycopersicum Esculentum Mill) - Bambang Wicaksono Hariyadi; Fauziatun Nizak; Intan Rohma Nurmalasari; Yeira Kogoya (Agricultural Science, 2019)
The purpose of this study is to examine the effect of the dose and time of NPK fertilizer application on the growth and yield of tomato plants (Lycopersicum esculentum Mill). The study was conducted from April to July 2018 at the Experimental Garden of the Faculty of Agriculture, Merdeka University Surabaya, on Ketintang Madya VII-2 Street Surabaya, East Java with altitude of ± 5 m above sea level. The study used Factorial Randomized Block Design (RBD) consisting of two factors with three replications and two sample plants. The first factor was NPK fertilizer doses (N1 = NPK 2 gr / plant; N2 = NPK 4 gr / plant; N3 = NPK 6 gr / plant) and the second factor was the time of NPK application (W1 = day 0; W2 = day 0-14; W3 = day 0-14-28). The results shows that the combination treatment of dose and application time of NPK has a very significant effect on plant height, number of leaves, total fruit number and total fruit weight of tomato plants. The combination treatment of N3W3 (NPK 6 gr / plant and day 0-14-28) appears to produce the highest growth and yield of tomato plants though, statistically (BNT 5%), this was not significantly different from the combination treatment of N2W3 (NPK 4 gr / plants and 0-14-28 days).